2007
DOI: 10.1007/s11273-007-9035-9
|View full text |Cite
|
Sign up to set email alerts
|

Soil and vegetation responses to hydrological manipulation in a partially drained polje fen in New Zealand

Abstract: Anthropogenic drainage causes loss of natural character in herbaceous wetlands due to increased soil oxygen penetration. We related vegetation gradients in a New Zealand polje fen to long-term effects of drains by using hydrological, edaphic and vegetation data, and a before-aftercontrol-impact (BACI) design to test responses to experimental drain closure. Soil profiles and continuous water level records revealed a site subject to frequent disturbance by intense but brief floods, followed by long drying period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Fast, bedmoving flows that disturb benthic invertebrates are unlikely. For instance, Sorrell et al (2007) found that water depth in the central main drain (N2) of Bullock Creek increased by up to seven times during a rainfall period, whereas velocity only doubled, from 0.2 to 0.4 m/s. This was still not fast enough to initiate movement of the gravel-bed substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fast, bedmoving flows that disturb benthic invertebrates are unlikely. For instance, Sorrell et al (2007) found that water depth in the central main drain (N2) of Bullock Creek increased by up to seven times during a rainfall period, whereas velocity only doubled, from 0.2 to 0.4 m/s. This was still not fast enough to initiate movement of the gravel-bed substrate.…”
Section: Discussionmentioning
confidence: 99%
“…and podocarp conifers (Podocarpaceae). The wetland is a mosaic of vegetation types, separated by a drainage network established during the first half of the twentieth century to convert the wetland into pasture (Sorrell et al 2007). Three site groupings have been identified within the BCW (Suren et al in press), based on differences in water chemistry, presence of aquatic vegetation, and substrate nature.…”
Section: Site Descriptionmentioning
confidence: 99%
“…This may explain why P was less accumulated in bulbs and leaves during growth in unflooded forests (Table 4). Nitrogen seems to be the limiting factor in the flooded sites as has been shown by Sorrell et al (2007) and Antheunisse et al(2006), probably due to the nitrogen removal by denitrification which commonly occurs in saturated soils (Rutherford and Nguyen 2004). Indeed, we have shown that bulb and leaf N:P ratios are highly correlated to total nitrogen in soils and not to soil phosphorus (Table 5).…”
Section: Biomass and Nutrient Plant Contentmentioning
confidence: 92%
“…While most studies of nutrient bioavailability matched up plant nutrient content with upland soil fertility (Aerts and Decaluwe 1994;Boerner 1984;Vitousek 1982), the importance of flooding in nutrient availability was widely highlighted (Ogden et al 2007) but still remained controversial as some recent studies showed that flooding re-establishment had no effect on N and P bioavailability (Ogden et al 2007;Sorrell et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, those species that have special traits for tolerating flooding may be replaced by generalists, less flood-tolerant alien species, and native taxa typical of drier forests [2], [31], [32]. The new conditions may support some rare species absent from wetlands; for example, terrestrial orchids seem to benefit from the shade and nutrient release in northern decayed-peat forests [33].…”
Section: Introductionmentioning
confidence: 99%